Reflecting on a community of practice for engineering education research capacity in Africa: who are we and where are we going? - Matemba, Esther; Smith, Lelanie; Wolff, Karin; Inglis, Helen; Mogashana, Disaapele; Jansen, Lauren; Gwynne-Evans, Alison; Campbell, Anita L.; Kwuimye, Cedrick; Nassar, Shamim; Magara, Irene; Kloot, Bruce; et al. (Australasian Journal of Engineering Education, 2023)
The Engineering Education Research Network in Africa (EERN-Africa) was created to enable connections between practitioners and researchers with a shared interest in African engineering education contexts. Recognising the importance of developing an African voice in the engineering education research space, the EERN-Africa community has interacted in a dynamic and dialogic way with our own teaching and research practices across diverse African contexts, with an ethical commitment to democratic and inclusive community-building. The objective of this paper is to reflect on the current status of the Community of Practice (CoP), and the challenges and opportunities in sustaining and growing the CoP. A collaborative analysis of perspectives on this emerging identity is presented, using an Appreciative Inquiry (AI) methodology and drawing on collective written reflections and discussions. Six broad themes on the value that the CoP has for both individuals and the group were identified: networking, capacity development, emotional support, impact on professional identity, social and environmental impact, and breaking borders. This paper contributes an approach for collaborative capacity-building in EER through a virtual CoP, underpinned by the spirit of ubuntu.
Keywords: Community of practice; Engineering education research; Engineering education practices; Capacity development; Ubuntu; Appreciative inquiry